2015
DOI: 10.1098/rspa.2015.0366
|View full text |Cite
|
Sign up to set email alerts
|

A chemo-mechanics framework for elastic solids with surface stress

Abstract: Elasticity problems involving solid-state diffusion and chemo-mechanical coupling have wide applications in energy conversion and storage devices such as fuel cells and batteries. Such problems are usually difficult to solve because of their strongly nonlinear characteristics. This study first derives the governing equations for three-dimensional chemo-elasticity problems accounting for surface stresses in terms of the Helmholtz potentials of the displacement field. Then, by assuming weak coupling between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Several studies have attempted to apply surface stress theory to energy storage materials and lithium-ion batteries. A general chemo-mechanics theory for elastic solids with surface stress was proposed by Gao et al [29]. However, for lithium-ion batteries, in particular, Cheng and Verbrugge [30] have shown that both the magnitude and distribution of stresses can be significantly affected by surface mechanics for nanoscale particles.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have attempted to apply surface stress theory to energy storage materials and lithium-ion batteries. A general chemo-mechanics theory for elastic solids with surface stress was proposed by Gao et al [29]. However, for lithium-ion batteries, in particular, Cheng and Verbrugge [30] have shown that both the magnitude and distribution of stresses can be significantly affected by surface mechanics for nanoscale particles.…”
Section: Introductionmentioning
confidence: 99%
“…Beside design perspectives, nano-wires and nano-tubes have enhanced electrochemical performance due to their robust electrical contact with the metallic current collector which enable each particle to contribute to the capacity [43,44]. A number of studies indicate the prominence of surface stress in nano-particles [52] as the prime reason behind their structural durability [53][54][55][56][57][58][59][60]. Furthermore, the effect of surface stress is dependent on the particle size (with decrease in particle size surface stress effect increases [61,62]), as well as the charging rate (with increase in charging rate, surface stress effect increases) [56].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the nonlinearity and coupling nature of this problem, Haftbaradaran and Qu [14] obtained the asymptotic solutions for three fundamental two-dimensional problems using a perturbation method. Gao et al [15] derived the governing equations for three-dimensional chemo-mechanical problems accounting for surface stresses. Similarly, a perturbation method is used and the nonlinear governing equations are reduced to a system of linear partial differential equations.…”
Section: Introductionmentioning
confidence: 99%